2023
DOI: 10.18063/ijb.v9i2.671
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of 3D-printed antibacterial hydrogel with benzyl isothiocyanate

Abstract: Benzyl isothiocyanate (BITC) is an isothiocyanate of plant origin, especially the mustard family, which has good antibacterial properties. However, its applications are challenging due to its poor water solubility and chemical instability. We used food hydrocolloids, including xanthan gum, locust bean gum, konjac glucomannan, and carrageenan as three-dimensional (3D)-printing food ink base and successfully prepared 3D-printed BITC antibacterial hydrogel (BITC-XLKC-Gel). The characterization and fabrication pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Recently, several commercial medical BC-based materials have been obtained: Biofill ® (Curitiba, Brazil) and Bioprocess ® (Curitiba, Brazil) for burns and ulcer therapy, Gengiflex ® (Curitiba, Brazil) to treat periodontal diseases, Dermafill ® (Londrina, Brazil) for effective wound and ulcer healing, Membracel ® (Curitiba, Brazil) to treat venous leg ulcers and lacerations, xCell ® (New York, NY, USA) for chronic wounds therapy, EpiProtect ® (Royal Wootton Bassett, UK) for burn wounds, and Nanoskin ® incorporated with silver ions (São Carlos, Brazil) [236,253]. BC and xanthan have great potential to be used in medicine as a biomaterial for wound dressing [254][255][256][257][258][259][260][261][262][263][264][265][266], drug delivery systems , and tissue engineering . Recently, many reviews on BC-based materials for biomedical applications have been reported.…”
Section: Applications Of Bc and Xanthanmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, several commercial medical BC-based materials have been obtained: Biofill ® (Curitiba, Brazil) and Bioprocess ® (Curitiba, Brazil) for burns and ulcer therapy, Gengiflex ® (Curitiba, Brazil) to treat periodontal diseases, Dermafill ® (Londrina, Brazil) for effective wound and ulcer healing, Membracel ® (Curitiba, Brazil) to treat venous leg ulcers and lacerations, xCell ® (New York, NY, USA) for chronic wounds therapy, EpiProtect ® (Royal Wootton Bassett, UK) for burn wounds, and Nanoskin ® incorporated with silver ions (São Carlos, Brazil) [236,253]. BC and xanthan have great potential to be used in medicine as a biomaterial for wound dressing [254][255][256][257][258][259][260][261][262][263][264][265][266], drug delivery systems , and tissue engineering . Recently, many reviews on BC-based materials for biomedical applications have been reported.…”
Section: Applications Of Bc and Xanthanmentioning
confidence: 99%
“…The publications on using xanthan to obtain medical materials have appeared relatively recently. So, in the last two decades, researchers have taken an interest in its future use in drug delivery, tissue engineering, as well as biocomposites with regenerative and antibacterial properties [261][262][263][264][265][266][274][275][276][277][278][284][285][286][287][288][289][321][322][323][324][325][326][327][328].…”
Section: Applications Of Bc and Xanthanmentioning
confidence: 99%
See 3 more Smart Citations